2018
DOI: 10.5565/rev/dag.355
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal analysis of the LST-NDVI relationship for the study of land cover changes and their contribution to urban planning in Monte Hermoso, Argentina

Abstract: Spatial and temporal analysis of the LST-NDVI relationship for the study of land cover changes and their contribution to urban planning in Monte Hermoso, Argentina AbstractThe aim of this work was to study the spatial distribution of Land Surface Temperature (LST) and its relationship with diverse urban land covers and the Normalized Difference Vegetation Index (NDVI). The study area was Monte Hermoso city, which is located in the southwest of Buenos Aires province, Argentina. To obtain the LST and NDVI param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
4
16
0
2
Order By: Relevance
“…Also, LST is influenced by land cover change and this is due to its role in the exchange of energy on the earth's surface, surface matter exchange and atmospheric processes (both physical and chemical) (Xiao et al 2007, Butuc, Moldovean 2011, Deng et al 2018. In a recent study, Ferrelli et al (2018) observed LST variation within diverse land covers in Monte Hermoso City, Argentina, as a consequence of urban growth and changes in vegetation cover. They thereafter concluded that the Spatiotemporal variation of LST values may indicate modifications in urban land cover.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, LST is influenced by land cover change and this is due to its role in the exchange of energy on the earth's surface, surface matter exchange and atmospheric processes (both physical and chemical) (Xiao et al 2007, Butuc, Moldovean 2011, Deng et al 2018. In a recent study, Ferrelli et al (2018) observed LST variation within diverse land covers in Monte Hermoso City, Argentina, as a consequence of urban growth and changes in vegetation cover. They thereafter concluded that the Spatiotemporal variation of LST values may indicate modifications in urban land cover.…”
Section: Introductionmentioning
confidence: 99%
“…They thereafter concluded that the Spatiotemporal variation of LST values may indicate modifications in urban land cover. The effect of population growth and the pressure or degradation it exerts on the environment are also other motivations to explore the relationship between land cover change and LST variations (Kaufmann et al 2007, Ferrelli et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LST and NDVI data derived from the Moderate Resolution Imaging Spectroradiometer (MODIS) for May 2001 over the Great Plains, USA, revealed negative correlations [14,15]. Correlations calculated from Landsat for individual days were found to be negative in many small study sites worldwide [16][17][18][19]. It was further shown that such relationships can be confined within a triangle or trapezoid space and related to land-cover classification and change detection [20], evapotranspiration and stomatal resistance [21], air temperature [22], leaf area index [23], phenology [24], crop yield [25], and evapotranspiration and soil moisture status [26].…”
mentioning
confidence: 99%
“…N. Moriasi et al, 2007;Hair, J. F., Hult, G. T. M., Ringle, C. M., & Sarstedt, 2013;Henseler et al, 2009). Nonetheless, in studies that examine the relationship between surface or near-surface air temperature and NDVI, local R 2 values higher than .50 are very common during the growing season (Colaninno and Morello, 2019;Ferrelli et al, 2018;Guha et al, 2018); this depends on the vegetation type, the month, and the spatial resolution of the data. Hence, corridors with local R 2 values lower than .50 may deem unsatisfactory for the purpose of this study and are excluded for the subsequent statistical analysis.…”
Section: Estimating the Relative Impact Of Ventilation Corridors On Mmentioning
confidence: 99%